Oxford Energy Forum, Issue 102 - Bassam Fattouh; Laura El-Katiri (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2015)
While the Middle East and North Africa (MENA) continues to play a pivotal role as the world's supplier of oil and, to a lesser extent gas, the collapse in global oil prices since mid-2014 has refocused the debate on the region's ability to use oil revenues to build sustainable and diversified economies that can one day function without oil, or at least reduce their heavy dependence on the export of only a single commodity. The Paris Climate Conference in December 2015 will provide an opportunity to the global community, including MENA countries, to contribute new vision and perspectives to the debate, and to engage proactively in leading regional green policy efforts. In this issue of the Oxford Energy Forum, we ask the question directly: can the MENA economies use this time to initiate the switch from fossil fuels to renewables, from wasteful energy consumption towards energy efficiency? Can the region re-invent itself? Can it 'grow green'?
Keywords: 330